Individual Team Productivity - A Conceptual Approach - Julia Müller; Thorsten Upmann; Joachim Prinz (Tinbergen Institute, 2013)
Teams, in both firms and in sports, jointly produce a product. While a fixed task is assigned to each member of a team, the individual team productivity of a worker or player is difficult to conceptualize. This is particularly true, if this concept is aimed to be operable on observable data. In this paper we, therefore, propose two versions of a new concept of individual team productivity which is closely related to eigenvalue centrality; accordingly we refer to it as eigenvalue productivity. For each version of eigenvalue productivity we provide an example demonstrating the operability of our concept.
Keywords: D24; J24; L23; L83; 330; individual team productivity; eigenvalue productivity; centrality; team production; team sports